Er-Cr-Ge Ternary System - Konyk, M.; Romaka, L.; Stadnyk, Yu.; Romaka, V.V.; Serkiz, R.; Horyn, A. (Physics and Chemistry of Solid State, 2019)
The isothermal section of the phase diagram of the Er–Cr–Ge ternary system was constructed at 1070 K over the whole concentration range using X-ray diffractometry, metallography and electron microprobe (EPM) analysis. The interaction between the elements in the Er−Cr−Ge system results in the formation of two ternary compounds: ErCr6Ge6 (MgFe6Ge6-type, space group P6/mmm, Pearson symbol hP13; a = 5.15149(3), c = 8.26250(7) Ǻ; RBragg = 0.0493, RF = 0.0574) and ErCr1-хGe2 (CeNiSi2-type, space group Cmcm, Pearson symbol oS16, a = 4.10271(5), b = 15.66525(17), c = 3.99017(4) Ǻ; RBragg = 0.0473, RF = 0.0433) at investigated temperature. For the ErCr1-xGe2 compound, the homogeneity region was determined (ErCr0.28-0.38Ge2; a = 4.10271(5)-4.1418(9), b = 15.6652(1)-15.7581(4), c = 3.99017(4)-3.9291(1) Ǻ).